Decision theory with a human face - Bradley, Richard, 1964 December 13- (Cambridge : Cambridge University Press, 2017)
When making decisions, people naturally face uncertainty about the potential consequences of their actions due in part to limits in their capacity to represent, evaluate or deliberate. Nonetheless, they aim to make the best decisions possible. In Decision Theory with a Human Face, Richard Bradley develops new theories of agency and rational decision-making, offering guidance on how'real' agents who are aware of their bounds should represent the uncertainty they face, how they should revise their opinions as a result of experience and how they should make decisions when lacking full awareness of, or precise opinions on relevant contingencies. He engages with the strengths and flaws of Bayesian reasoning, and presents clear and comprehensive explorations of key issues in decision theory, from belief and desire to semantics and learning. His book draws on philosophy, economics, decision science and psychology, and will appeal to readers in all of these disciplines.
Title from publisher's bibliographic system (viewed on 24 Oct 2017).
Keywords: Bayesian statistical decision theory; Decision making -- Mathematical models; Uncertainty -- Mathematical models